Abuse and neglect among Ethiopian children and adolescents. (May 2022) - Lima, Nadia Nara Rolim; de Moura Gabriel, Italo Wanderson; Pires, Jeully Pereira; Neto, João Cruz; da Silva, José Italo Monte; Júnior, José Ribamar Monteiro; Neto, Modesto Leite Rolim
Abstract: Given the dramatic situation observed in Ethiopia, the biggest humanitarian crisis in decades, children and adolescents have been the most affected. The country experiences climate change and disarrays in the political structure of the state, which increases the risk of insecurity, displacement, and protection. The outlook tends to remain in 2022 due to the expansion of the conflict and the decrease in the access of partners' humanitarian aid groups to the affected regions. The country has high rates of malnutrition, low vaccination coverage, need for educational assistance, water, and sanitation emergency, lack of services to protect against violence, and high rates of children unaccompanied by their families. During the conflict, children, often to save their lives - because they have extended families or unhealthy inter-family relationships - end up looking for work on the streets and falling into a situation of vulnerability. In this context, they become constant victims of sexual abuse and physical violence, leaving deep marks. Still, the country's folk traditions fall back on the girls, significantly in a negative way, when genital mutilation and child marriage are in considerable proportion among girls in the country. However, the humanitarian actions did not concern themselves with referring to the particular needs of adolescent girls, including the involvement of caregivers to reduce the risk of violence. In this sense, it is important to point out that the increase in discrimination, stigmatization, and xenophobia contribute negatively to local tensions and to the improvement of vulnerability and social risk of children and adolescents. Therefore, there is a need for interventions to multisectoral nutrition, due to the prevalence of thinness and stunting that are above the threshold level of public health importance, and the need for urgent humanitarian assistance care to the more than 15 million children affected by this unprecedented crisis. Highlights: Across the Ethiopia, more than 1.2 million children under five years need treatment for severe acute malnutrition. 5.7 million women/children need emergency protection services. At least 204, 500 unaccompanied/separated children need family tracing and reunification services.